Application of nanocellulose composites in the environmental engineering as a catalyst, flocculants, and energy storages: a review - Pagliaro, Mario; Ciriminna , Rosaria; Yusuf, Mohammad; Eskandarinezhad, Sara; Wani, Irshad Ahmad; Ghahremani, Mina; Rezaei Nezhad, Zahra (Journal of Composites and Compounds, 2021)
Nanocellulose, the most promising bionanomaterial, is obtained either from the degradation of natural polymers or by the activity of bacteria and microorganisms. These biomaterials present various advantages, including full recyclability, biodegradability, and lack of harmful effects on the human body and environment. Furthermore, nanocelluloses are candidates to fabricate thin transparent layers, fibers, hydrogels, and aerogels due to their remarkable optical, thermal, and mechanical behaviors, including high crystallinity, Young’s modulus, and porosity content. These exceptional properties present the superb potential of these materials for the device of environmentally engineered tenable products. This paper presents an outline of the contemporary nanocellulose research works as well as details and information on the nanocellulose materials, especially the synthesis process of composites, along with the areas in which these materials can be utilized, such as energy, flocculant, pollution sensors, and catalysts, to respond to the rising requests of these materials.